IMPLEMENTATION OF THINK-PAIR-SHARE STRATEGY THROUGH DISCOVERY LEARNING IN READING DESCRIPTIVE TEXT SMPN 1 TIRTAMULYA - Putri, Amalia Dwi; Samsi, Yogi Setia; Miftakh, Fauzi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
Reading is one of the most crucial aspects of English language development in school. Strategy or learning method has an important role to improve the students’ ability in reading descriptive text. Think-Pair-Share and Discovery learning were used to facilitate students' reading through descriptive text. The research intended to implement Think-Pair-Share and Discovery learning in reading descriptive text. The research design used a case study. The participants are one teacher and one student at English class of eighth grade. Meanwhile, the instruments used to collect data are observation checklist and interview guide. Thus, the researcher is analyzed by using data reduction, data display, and drawing conclusion and verification. The findings show insight into the positive outcomes of employing the TPS strategy and the discovery learning method when teaching and learning descriptive text. The conclusion based on the observations and interview provided, the researcher has concluded that the Think-Pair-Share strategy and the discovery method are strategies and methods utilized by English teacher to teach reading descriptive texts in the eighth grade classroom. This collaborative approach not only boosts students' self-confidence but also encourages them to be more enthusiastic and willing to solve problems together. Think-Pair-Share strategy through the discovery learning method has been shown to better students' learning outcomes and reading comprehension abilities.